Locus of Control, Interest in Schooling and Science Achievement of Some Deaf and Typical Secondary School Students in Nigeria - Olatoye, R. Ademola; Aanu, E. Mosunmola (Journal of the American Academy of Special Education Professionals, 2010)
This study compared locus of control, interest in school and science achievement of typical and deaf secondary school students. The study also investigated influence of students’ locus of control and interest in school on general science achievement. Seventy two (72) deaf and 235 typical children were purposively selected from eight secondary schools from Oyo and Ogun States in Nigeria. Three instruments were used to collect data. They are: Locus of control questionnaire, Interest in schooling questionnaire and Science achievement test. Interest in school and locus of control when taken together accounted for 25.6% of the total variance in science achievement (R[superscript 2]= 0.256, p < 0.05). There was significant difference in locus of control and interest in school between deaf and typical children. Typical children significantly tended towards external locus of control ( t = 4.416, p < 0.05) and also had more interest in schooling (t = 5.747, p < 0.05) than their deaf counterparts. Typical children also performed significantly better than their deaf counterparts (t = 7.294, p < 0.05). Teachers should make schooling more interesting especially to deaf students. Necessary facilities should be provided for the deaf students to enhance their teaching so that their achievement in science will be at par with their hearing counterparts.